REGULASI QRIS ATAS PENGEMBANGAN METODE PEMBAYARAN DIGITAL DI WILAYAH ASEAN - Moh. Bahrul Ulum; Nuzulia Kumala Sari; Halif (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2026)
This study aims to examine the regulatory framework of the Quick Response Code Indonesian Standard (QRIS) as a legal instrument that strengthens Indonesia’s digital payment system and promotes its integration within the ASEAN region. The research employs a normative legal method using qualitative-descriptive analysis, based on a review of legal regulations, academic sources, and empirical data related to QRIS implementation at both national and regional levels. The findings reveal that the regulations issued by Bank Indonesia and the Ministry of Finance have provided a robust legal basis for ensuring efficiency and security in Indonesia’s digital payment ecosystem. Furthermore, the cross-border payment collaboration between Indonesia and Thailand serves as evidence of QRIS’s potential to enhance cross-border economic transactions and reinforce Indonesia’s role in regional digital diplomacy. The discussion emphasizes that strengthening the legal framework, data protection, and cybersecurity is essential to maintaining QRIS’s sustainability amid global digital transformation. Overall, QRIS acts not only as a digital payment instrument but also as a manifestation of national economic sovereignty, fostering efficiency, inclusivity, and competitiveness in the global digital economy.